Elderly vulnerability: concept development - Keylla Talitha Fernandes Barbosa; Maria das Graças Melo Fernandes
ABSTRACT Objective: Propose the concept of vulnerability of the elderly based on the Hybrid Concept Development Model. Method: Methodological study with a qualitative approach, based on the theoretical-methodological framework of the Hybrid Concept Development Model. Initially, an integrative literature review was carried out, followed by empirical collection through semi-structured interviews with 12 professionals. As a method of analysis of the interviews, the Grounded Theory was used. The final analytical phase constituted the interface between theoretical and empirical evidence. Results: When carrying out the theoretical survey, it became possible to outline the attributes, antecedents and consequences of the studied phenomenon. After analyzing the empirical data, two phenomena emerged: Unveiling the multiple changes arising from the human aging process; and Understanding the multiple dimensions of the elderly person's vulnerability construct. Final considerations: The vulnerability of the elderly person consists of a multifaceted construct, in which individual and collective conditions interact with each other.